NO2 Sensing Properties of Cr2WO6 Gas Sensor in Air and N2 Atmospheres - Wu, Yi; Yan, Meng; Tian, Chen; Liu, Yuhang; Hua, Zhongqiu (Frontiers in Chemistry, 2020)
Gas sensors were fabricated from Cr2WO6 nanoparticles for NO2 detection. Low dimensional materials Cr2WO6 were prepared by a wet chemistry method followed by hydrothermal treatment. The morphology of the nanoparticles and their sensing properties to NO2 were investigated in both dry and humid conditions. Additionally, the sensing response was also characterized in a non-oxygen condition. It was concluded that the sensor responses in N2 conditions were higher than that in air conditions at 200°C. Moreover, the sensing characteristics were inhibited by water vapor at 200°C. The oxygen adsorption behavior was also investigated to verify the basic sensing mechanism of Cr2WO6 in the absence and presence of NO2 and water vapor separately. Based on the power law response, it was indicated that both NO2 and water vapor have a strong adsorption ability than oxygen ions of Cr2WO6 sensors.